Investigating the Impact of the External Environment and Benchmark Characteristics on the China-Pakistan Economic Corridor’s Construction: A COVID-19 Perspective - Xu, Aidi; Pitafi, Abdul Hameed; Shang, Yunfeng (Frontiers in Psychology, 2022)
The economic stability of a country such as Pakistan is dependent on the construction of megaprojects such as the China-Pakistan Economic Corridor (CPEC). However, certain external factors and project characteristics may delay the construction of infrastructure projects; scholars have not investigated the development of CPEC from this perspective. In addition, the COVID-19 outbreak has hindered CPEC initiatives. This analysis will examine the effect of external environment factors on CPEC, and benchmark the project’s effects on economic stability through CPEC’s development by incorporating 523 samples obtained from employees of various CPEC projects. Structural equation modeling was used to analyze all hypotheses proposed here on AMOS 21.0 tools. According to the findings of this study, the CPEC external environment and project benchmark characteristics have a negative effect on the construction of CPEC development. Furthermore, the development of CPEC is found to have a significant effect on economic stability. However, fear of COVID-19 has weakened the relationship between CPEC development and economic stability. Finally, we also discuss the implications and limitations of the study